The Editor's Corner; Meet ACE Authors - R. E. Stevenson (Journal of Applied Communications, 1970)
Editor's Corner and editorial back matter for vol. 53, no. 3 (July-Sept. (1970) of ACE, the official journal of the American Association of Agricultural College Editors.